Inclusive Paradigm –Religion Pluralism on Al-Quran Perspective (Qs. Al-Baqarah/2: & Qs. Ali Imran/3: 64 Analysis) - Aisma Maulasa; M. Gazali Rahman (Al-Ulum, 2014)
This writing is discussing Alquran perspective about the attitude which should be owned by every Moslem in facing religion pluralism as something is possible and factual. By doing deep analysis on QS AlBaqarah /2: 136-137 and QS Ali Imran /3: 64, it is clear that pluralism is factual and be sunnatulah which should be exclaimed its truth. The three verses are also claim five ideal forms which should be had and implemented by all Moslem in regulating their interaction with other religion followers. As the biggest inspiration of a Moslem, then the finding meaning on Alquran verses will minimalize even erupt all exclusive paradigm on religion which for long time constraint the harmony of religion relationship. Exclusive religion bears, because there is misunderstanding and less of understanding about Alquran verses.